2022
DOI: 10.3390/ijerph20010102
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Cardiovascular Lifestyle Risk Factors among Pregnant Women in Burkina Faso: Evidence from a Cross-Sectional Study

Abstract: Data on lifestyle risk factors for cardiovascular diseases, such as smoking, alcohol consumption, inadequate physical activity, and insufficient consumption of fruits and vegetables, in pregnant women in Africa, are scarce. This study aimed to estimate the prevalence of cardiovascular lifestyle risk factors among pregnant women in Burkina Faso and identify their associated factors. Pregnant women who attended antenatal care services between December 2018 and March 2019 were included in this study. A modified P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
2
0
0
Order By: Relevance
“…Similar to our research ndings, a study conducted in Ethiopia revealed that pregnant women residing in rural areas had elevated odds of experiencing Anemia in Pregnancy compared to those in urban areas [29]. Likewise, in Burkina Faso, research indicated that pregnant women in rural regions were more prone to anemia compared to their urban counterparts, aOR 1.33 (95%CI:1.01-1.74) [30]. Furthermore, a research endeavor sought to assess variances between urban and rural areas concerning adverse outcomes related to pregnancy.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our research ndings, a study conducted in Ethiopia revealed that pregnant women residing in rural areas had elevated odds of experiencing Anemia in Pregnancy compared to those in urban areas [29]. Likewise, in Burkina Faso, research indicated that pregnant women in rural regions were more prone to anemia compared to their urban counterparts, aOR 1.33 (95%CI:1.01-1.74) [30]. Furthermore, a research endeavor sought to assess variances between urban and rural areas concerning adverse outcomes related to pregnancy.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our research ndings, a study conducted in Ethiopia revealed that pregnant women residing in rural areas had elevated odds of experiencing Anemia in Pregnancy compared to those in urban areas [30]. Likewise, in Burkina Faso, research indicated that pregnant women in rural regions were more prone to anemia compared to their urban counterparts, aOR 1.33 (95%CI:1.01-1.74) [31]. Furthermore, a research endeavor sought to assess variances between urban and rural areas concerning adverse outcomes related to pregnancy.…”
Section: Discussionsupporting
confidence: 88%